Implementing Technology Acceptance Model to measure ICT usage by smallholder farmers - Agus Trihandoyo; Dana Santoso Saroso; Satya Arisena Hendrawan (SINERGI, 2023)
In the era of industry 4.0, especially in the agricultural sector, using ICT as a communication and information-gathering medium for farmers is crucial. However, the ICT adoption level by smallholder farmers varies greatly. This study investigates the elements influencing the ICT adoption level and utilization and explores the application of the TAM to smallholder farmers. Using descriptive quantitative methodology on three villages in Ngawi regency, East Java (N=53), this study indicated that smartphone usage in the research location was extremely high at 90.5%. A Spearman correlation value of 0.24 indicates a relationship between the PU and the education level of farmers. T-Test Two Means Independent was used to compare respondents' perception of ICT utilization through Perceived Use (PU) and Perceived Ease of Use (PEU); PU's average value of 17.5 was greater than PEU's average value of 13.9. It was determined that ICT perceived usefulness was felt more important than perceived ease of use by the respondents in their daily activities. Additionally, this study recommends that agriculture services development necessitates strategies to create ICT usefulness through smartphones. Such strategies will help increase the ICT effective adoption, reducing information gaps and raising the wealth of smallholder farmers.